2018
DOI: 10.1590/s0100-204x2018000400014
|View full text |Cite
|
Sign up to set email alerts
|

Injection of liquid swine slurry and effects on properties of a Nitossolo Vermelho

Abstract: The objective of this work was to evaluate the superficial and injected applications of swine slurry and urea to the soil, regarding their effects on the physical properties of a Nitossolo Vermelho distroférrico under a no-tillage system. The treatments were: injected slurry into the groove with a liquid swine slurry injector (LSSI); slurry on surface, applied on the lines by the LSSI kept raised; urea injected by opening the groove with the LSSI and distributed manually; and corn, under no-tillage, as a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Adesanya et al (2016) found that mean weight diameter was significantly greater in the manure treatment compared with the control soil; this is likely due to an increase in SOC after manure is applied to the soil. Rech et al (2018) found no change in mean weight diameter in a clay soil when liquid swine manure or inorganic fertilizer was applied. Tavares et al (2019) found that the mean weight diameter increased the most when only 25 m 3 ha −1 yr −1 liquid swine manure was applied (39%) and increased the least when 75 m 3 ha −1 yr −1 liquid swine manure was applied (15%), which suggests that the composition of the swine manure is more important than the rate that it is applied.…”
Section: Aggregate Stabilitymentioning
confidence: 85%
See 3 more Smart Citations
“…Adesanya et al (2016) found that mean weight diameter was significantly greater in the manure treatment compared with the control soil; this is likely due to an increase in SOC after manure is applied to the soil. Rech et al (2018) found no change in mean weight diameter in a clay soil when liquid swine manure or inorganic fertilizer was applied. Tavares et al (2019) found that the mean weight diameter increased the most when only 25 m 3 ha −1 yr −1 liquid swine manure was applied (39%) and increased the least when 75 m 3 ha −1 yr −1 liquid swine manure was applied (15%), which suggests that the composition of the swine manure is more important than the rate that it is applied.…”
Section: Aggregate Stabilitymentioning
confidence: 85%
“…Two of the swine manure papers that were reviewed reported an increase in bulk density and a decrease in porosity after manure was applied to clayey soils (Rech et al., 2018; Scheid et al., 2020) (Table 5). Soil bulk density did decrease over time with annual swine manure application compared with the control that did not receive manure (Scheid et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This set was adapted from a no-till sowing machine, which has a front cutting disc and a furrower stem, in which the posterior face is located the output of the jet of PS. Thus, incorporations were performed in furrows of 0.12 m deep and spaced 0.35 m, with average width soil mobilization of 0.10 m (Rech et al, 2018). The PS superficial applications were made with the same equipment, but with the incorporation set suspended over the ground.…”
Section: Methodsmentioning
confidence: 99%